Regularizers for Vector-Valued Data and Labeling Problems in Image Processing - Lellmann, J.; Schnörr, C. (Управляющие системы и машины, 2011)
Дан обзор последних результатов в области регуляризаторов, основанных на полных вариациях, применительно к векторным данным. Результаты оказались полезными для хранения или улучшения мультимодальных данных и задач разметки на непрерывной области определения. Возможные регуляризаторы и их свойства рассматриваются в рамках единой модели. The review of recent developments on total variation-based regularizers is given with the emphasis on vector-valued data. These have been proven to be useful for restoring or enhancing data with multiple channels, and find particular use in relaxation techniques for labeling problems on continuous domains. The possible regularizers and their properties are considered in a unified framework. Наведено огляд останніх результатів у галузі регуляризаторів, що базуються на повних варіаціях, стосовно векторних даних. Результати виявилися корисними для зберігання та покращення мультимодальних даних і задач розмітки на неперервній області визначення. Можливі регуляризатори та їх властивості розглядаються в рамках єдиної моделі.